The mythology of work : how capitalism persists despite itself - Fleming, P. (Peter), 1972- (London : Pluto Press, 2015)
There was once a time when 'work' was inextricably linked to survival. But what was once an integral part of life has slowly morphed into a painful and meaningless routine, colonising almost every part of our lives. As our society is transformed into a factory that never sleeps, work becomes a universal reference point for everything else, devoid of moral or social worth. Blending theory with accounts of job-related suicides, office-induced paranoia, fear of relaxation, managerial sadism and cynical corporate social responsibility campaigns, Fleming provides a damning report on the way work consumes our lives in modern capitalist society. -- from back cover.
Introduction : Once upon a time, man invented work -- The factory that never sleeps -- Planet of work -- What Is managerialism? -- Viral capitalism in the bedroom -- Corporate ideology as false truth telling -- Critique of dialogical reason -- Conclusion : Inoperative critique and the end of work.
Includes bibliographical references (pages 200-207) and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Work environment -- Social aspects; Capitalism -- Social aspects; Industrial sociology; Labor; Work; Neoliberalism; Work -- Political aspects; Human capital; Electronic books